Impact of heat stress on the growth performance and retail meat quality of 2nd cross (Poll Dorset × (Border Leicester × Merino)) and Dorper lambs. (November 2021) - Zhang, Minghao; Warner, Robyn D.; Dunshea, Frank R.; DiGiacomo, Kristy; Joy, Aleena; Abhijith, Archana; Osei-Amponsah, Richard; Hopkins, David L.; Ha, Minh; Chauhan, Surinder S.
ABSTRACT: The present study investigated the impact of heat stress and genetics on lamb growth performance and meat quality. Forty-eight Dorper and 2nd cross [Poll Dorset × (Border Leicester × Merino)] lambs (38‐–42 kg; 4–5 months old) were allocated to either thermoneutral [TN; 18–21 °C, 45–55% relative humidity (RH)], or heat stress (HS; 28 °C–38 °C, 40–60% RH) conditions in a 2 × 2 factorial design for 2 weeks. Compared with 2nd cross, Dorper lambs had a lower respiration rate (RR) and rectal temperature (RT), and exhibited less decline in body weight under HS. 2nd cross lambs showed a higher body weight gain than Dorpers under TN conditions. HS increased a * and chroma of the Longissimus thoracis et lumborum (LTL) from 2nd cross lambs over 10 days of display, but had no impact on Dorper LTL. In conclusion, Dorpers showed higher heat tolerance compared with 2nd cross lambs during the 2 weeks HS.